THE EFFECT OF FDI, NET EXPORTS AND INFLATION ON ECONOMIC GROWTH IN ASEAN-5 FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Ulfa, Ulfa Nur Halimah; Supaijo; Siska Yuli Anita (I-Finance Journal, 2025)
This study aims to determine and examine the effect of FDI, net exports, and inflation on economic growth in the ASEAN-5 emerging market countries. The research method used is quantitative. The population in this study consists of five ASEAN countries (Indonesia, Malaysia, the Philippines, Thailand, and Vietnam). The sample used in this study employs purposive sampling, which determines the sample by selecting members of the population according to the criteria required by the research. The data analysis technique in this study uses panel data regression with Chow and Hausman tests. The hypothesis testing series consisted of the F test, the test, and the coefficient of determination (R2). The results of this study prove that partial foreign direct investment does not have a positive and significant effect on economic growth. Net exports do not have a positive and significant effect on economic growth. Inflation has a significant positive effect on economic growth. Based on the results of the Chow test, Hausman test, and LM test, the Common Effect model is more appropriate for use in this study. The conclusion is that, simultaneously, foreign direct investment, net exports, and inflation have a significant effect on economic growth in the ASEAN-5 emerging market countries from 2020 to 2024